2024
DOI: 10.3390/antiox13030291
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Oxidative Stress and Ferroptosis in Triple-Negative Breast Cancer Cells by Niclosamide via Blockade of the Function and Expression of SLC38A5 and SLC7A11

Marilyn Mathew,
Sathish Sivaprakasam,
Gunadharini Dharmalingam-Nandagopal
et al.

Abstract: The amino acid transporters SLC38A5 and SLC7A11 are upregulated in triple-negative breast cancer (TNBC). SLC38A5 transports glutamine, methionine, glycine and serine, and therefore activates mTOR signaling and induces epigenetic modifications. SLC7A11 transports cystine and increases the cellular levels of glutathione, which protects against oxidative stress and lipid peroxidation via glutathione peroxidase, a seleno (Se)-enzyme. The primary source of Se is dietary Se-methionine (Se-Met). Since SLC38A5 transpo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…It is also important to point out here that the potency of niclosamide as an inhibitor of SLC7A11 (IC 50 , <0.25 µM) is greater than most of the inhibitors, including erastin, reported thus far in the literature [78]. We found a similar IC 50 value in triple-negative breast cancer cells [32]. Even though derivatives of erastin have been developed recently with a much greater potency to inhibit SLC7A11 (IC 50 values in the low-nanomolar range) [79], niclosamide may have an advantage in terms of therapeutic use for cancer therapy because of its feature as an already FDA-approved drug that has been in use in humans for several decades.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…It is also important to point out here that the potency of niclosamide as an inhibitor of SLC7A11 (IC 50 , <0.25 µM) is greater than most of the inhibitors, including erastin, reported thus far in the literature [78]. We found a similar IC 50 value in triple-negative breast cancer cells [32]. Even though derivatives of erastin have been developed recently with a much greater potency to inhibit SLC7A11 (IC 50 values in the low-nanomolar range) [79], niclosamide may have an advantage in terms of therapeutic use for cancer therapy because of its feature as an already FDA-approved drug that has been in use in humans for several decades.…”
Section: Discussionsupporting
confidence: 72%
“…Based on our previous studies with breast cancer cells [ 31 , 32 ], the ability of niclosamide to induce intracellular acidification and inhibit SLC38A5 is expected to suppress macropinocytosis. We tested this by monitoring macropinocytosis-mediated cellular entry of TMR-dextran in all four colon cancer cell lines with a 30-min preincubation with and without niclosamide (5 μM).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, it was shown that SLC38A5 could transport selenomethionine (Se-Met), the most common dietary source of selenium. Since the selenoenzyme GPX4 is a critical component of the antioxidant machinery in TNBC cells, the possible involvement of SLC38A5 in the delivery of selenium to cancer cells in the form of Se-Met may represent a novel function of the transporter in promoting cancer growth [109]. Fan et al showed that Se-Met is an activator of Nrf2, an important transcription factor associated with the antioxidant mechanism [110].…”
Section: Amino Acids and Oxidative Stress In Breast Cancermentioning
confidence: 99%